PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KARAKTER KOMUNIKATIF SISWA DALAM PEMBELAJARAN IPA FISIKA KELAS VII SMP NEGERI 20 PEKANBARU - Melsa Atsawati; Mitri Irianti; Azhar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aimed to determine the increase in students’ communicative character through the implementation of Snowball Throwing learning model on the states of matter and the density. The research subjects were 38 students in class VII7 SMPN 20 Pekanbaru. The design of this research was a pre-experimental with one group pretest-posttest design. Data collection Instruments in this research was students' communicative character questionnaire consisting of 17 Statements. Data were analyzed using descriptive analysis and improvement N-gain. The results showed increase on communicative character descriptor is 0,37 with predicate medium. So, it can be concluded that science physics learning applying Snowball Throwing learning model effective to improve the students' communicative character in calss VII7 SMP 20 Pekanbaru.Key Words: Communicative Character, Snowball Throwing